PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KARYAWAN TERHADAP KINERJA KARYAWAN PADA PT. DUNIA MARINE PRODUCTS DI MAKASSAR - Hj. Nuraini Rasyid (Jurnal Bisnis dan Kewirausahaan, 2018)
This study aims to determine the extent to which the influence of organizational culture on employee performance at PT. World Marine Products in Makassar and to find out how far the influence of employee motivation on employee performance at PT. Dunia Marine Products in Makassar as well as to analyze the most dominant variable affect on employee performance at PT. Dunia Marine Products In Makassar From the results of research indicates that the organizational culture and motivation have a positive and significant influence on employee performance at PT. Dunia Marine Products in Makassar, From the results of testing the hypothesis that has been done then it can be concluded that the most dominant variable affect the employee performance at PT. Dunia Marine Products in Makassar is an organizational culture.